1971
DOI: 10.1111/j.1432-1033.1971.tb01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Corticosterone in the Isolated Perfused Rat Liver

Abstract: [4-14C]Corticosterone was perfused through isolated livers from male and female rats. Bile, perfusate and liver tissue were extracted and analysed separately. No specific differences were observed in the distribution of various isomers of corticosterone metabolites isolated from these three sources. However, the radioactive metabolites with the chromatographic property of steroid glucuronides were mainly present in the bile. Male rat livers metabolized corticosterone into the following 20-hydroxy compounds : 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1971
1971
1981
1981

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The faecal extract was partitioned between 150 ml of aqueous ethanol spect to NaCI. Details of this procedure have been presented in previous publications [11,12]. The free steroids were eluted from the column between 100 to 160 ml of effluent and the steroid monosulphate fraction was collected between 240-460 ml.…”
Section: Extraction and Purification Of Faecal 8teroichmentioning
confidence: 99%
“…The faecal extract was partitioned between 150 ml of aqueous ethanol spect to NaCI. Details of this procedure have been presented in previous publications [11,12]. The free steroids were eluted from the column between 100 to 160 ml of effluent and the steroid monosulphate fraction was collected between 240-460 ml.…”
Section: Extraction and Purification Of Faecal 8teroichmentioning
confidence: 99%
“…At present, the data may be reconciled with the hypothesis that pregnane-3,11,20,2l-tetrols are primary metabolites in male rats whereas sulphates of 3,11,15,21-tetrahydroxypregnan-20-ones are primary metabolites in female rats [5]. In the conventional rats, steroid sulphates are hydrolyzed by microorganisms in the intestinal tract [16]. Steroids containing a 20-0x0 group may undergo 16 or 21-dehydroxylation whereas steroids with a 16a,20-or 20,21-dihydroxy structure are not susceptible to this type of microbial attack [6].…”
Section: Itmentioning
confidence: 52%
“…The main part of the radioactive steroids in urine from both germfree and conventional female rats was found in the monosulphate fraction and several of these steroids have been identified. No such conjugates were found in urine from the male rats [1,2]. The radioactive metabolites in the free steroid fraction were more polar in excreta from male than in those from female conventional rats [l].…”
mentioning
confidence: 99%
“…Evidence has been presented that these compounds are metabolites of 1601-hydroxylated steroids [1,4] and that a t least in the rat the conversion is carried out mainly by intestinal microorganisms in reactions involving the intermediate formation of A16-unsaturated steroids. I n a previous study from this laboratory, it was shown that 3P-hydroxy-5,16-pregnadien-20-one was efficiently converted into 3B-hydroxy-17a-pregn-5-en-20-one when incubated with caecal contents from rats under anaerobic conditions [i].…”
mentioning
confidence: 99%